(untitled) (ENTHYMEMA, 2020)
The article proposes a focus on the reading and writing machines in If on a Winter’s Night a Traveler by Italo Calvino. This aspect of the novel reflects Calvino’s prediction of a literary automaton we find in his essay “Cybernetics and ghosts”. It’s also true that Marana’s writing machine has the same combinatory system and parodist aim of the device described in the 3th book of Gulliver’s Travels. Moreover, the reading machine in Calvino’s novel dissolves the book in a dust of melted words, an image that may trace back to Rabelais’ myth of parolles gelées. These references give us the possibility to explore the fabulous element of If on a Winter’s Night a Traveler.